A novel inhibitor of ARfl and ARv7 induces protein degradation to overcome enzalutamide resistance in advanced prostate cancer - Yan Li; Ya Chu; Guangjiang Shi; Xiaobin Wang; Wanli Ye; Chun Shan; Dajia Wang; Di Zhang; Wei He; Jingwei Jiang; Shuqian Ma; Yuhong Han; et al. (Elsevier, 2022)
Enzalutamide (ENZ) is a second-generation androgen receptor (AR) antagonist used for the treatment of castration-resistant prostate cancer (CRPC) and reportedly prolongs survival time within a year of starting therapy. However, CRPC patients can develop ENZ resistance (ENZR), mainly driven by abnormal reactivation of AR signaling, involving increased expression of the full-length AR (ARfl) or dominantly active androgen receptor splice variant 7 (ARv7) and ARfl/ARv7 heterodimers. There is currently no efficient treatment for ENZR in CRPC. Herein, a small molecule LLU-206 was rationally designed based on the ENZ structure and exhibited potent inhibition of both ARfl and constitutively active ARv7 to inhibit PCa proliferation and suppress ENZR in CRPC. Mechanically, LLU-206 promoted ARfl/ARv7 protein degradation and decreased ARfl/ARv7 heterodimers through mouse double minute 2-mediated ubiquitination. Finally, LLU-206 exhibited favorable pharmacokinetic properties with poor permeability across the blood-brain barrier, leading to a lower prevalence of adverse effects, including seizure and neurotoxicity, than ENZ-based therapies. In a nutshell, our findings demonstrated that LLU-206 could effectively inhibit ARfl/ARv7-driven CRPC by dual-targeting of ARfl/ARv7 heterodimers and protein degradation, providing new insights for the design of new-generation AR inhibitors to overcome ARfl/ARv7-driven CRPC.